Pengaruh Perencanaan Strategis Dan Kinerja SDM Dengan Titik Berat Pada Program Blitar Keren Terhadap Pencapaian Iku Pada Pemerintah Daerah Kota Blitar - Bekti Abdillah Kholik (Universitas Islam Kadiri, 2022)
Strategic planning is very necessary in order to achieve the Key Performance Indicators (KPI) with the right goals and objectives. Besides that, reliable and professional HR performance is also needed to carry out the duties and functions related to the strategic planning that has been determined. The determination of the Main Indicators must meet the characteristics and criteria of adequate Performance Indicators for measuring the performance of the Regional Work Units in order to achieve the Blitar Keren Program. The purpose of this study was to determine the effect of Strategic Planning with Emphasis on the Blitar Keren Program on Achievement of KPI (Key Performance Indicators) in Blitar City, determine the effect of HR performance with Emphasis on the Blitar Keren Program on Achievement of KPI (Main Performance Indicators) City Blitar. and to determine the simultaneous effect of strategic planning and HR performance with the emphasis on the Blitar Keren Program on the Achievement of the KPI (Key Performance Indicators) of Blitar City. This type of research is a quantitative research with a descriptive approach. The primary data collection technique was using a questionnaire questionnaire. Meanwhile, secondary data collection uses BPS data and data sourced from the Blitar city government. the number of samples in this study were 62 respondents. While the method used in data analysis in this study is multiple linear regression analysis. The results showed that 1) Strategic Planning had a positive and significant direct effect on the Achievement of KPIs (Key Performance Indicators) with the emphasis on the Blitar Keren. Weight on the Blitar Keren Program 3) Strategic Planning and HR performance have a direct positive and significant impact on the Achievement of KPI (Key Performance Indicators) with an emphasis on the Blitar Keren Program